Optimasi Biaya Konstruksi dengan Pendekatan Life-Cycle Cost Pagar Panel Precast dan Pagar Batako di Kediri - Jhody Hendarwan; Imam Mustofa (Institut Teknologi Garut, 2026)
The rapid development of construction technology demands building systems that are efficient in terms of cost, time, and quality. In the context of light infrastructure such as perimeter fencing, the choice of construction method significantly affects the total project cost over its service life. This study aims to compare the economic efficiency of precast concrete panel fences and conventional concrete block (batako) fences using a Life-Cycle Cost (LCC) analysis approach. This research adopts a quantitative–comparative method based on the Life-Cycle Costing Manual (Fuller & Petersen, 1995) and ISO 15686-5:2017 standards. Data were obtained from an actual fencing project in Kediri City, including cost estimates (RAB), material volumes, construction duration, and maintenance costs. The analyzed parameters include Capital Expenditure (CAPEX), Operational Expenditure (OPEX), and Event Costs, using an 8% discount rate and a 20-year project service life. The results show that the precast fence system yields a total Net Present Cost (NPC) of IDR 608.88 million, while the concrete block fence reaches IDR 848.12 million, indicating a cost efficiency of approximately 39%. In addition, the precast system requires only 14 days for installation, which is 58.8% faster than the concrete block system that requires 34 days. In terms of dimensions, the precast fence uses 63.9% less material volume and has a lighter structural weight. Overall, the precast concrete panel fence demonstrates higher cost efficiency, faster construction time, and better material durability under the humid tropical climate of Kediri.